Path induced coherent energy transfer in light-harvesting complexes in purple bacteria - Sun, Kewei (2014)
Features of path dependent energy transfer in a dual-ring light-harvesting (LH2) complexes (B850) system have been examined in detail systematically. The Frenkel-Dirac time dependent variational method with the Davydov D1 Ansatz is employed with detailed evolution of polaron dynamics in real space readily obtained. It is found that the phase of the transmission amplitude through the LH2 complexes plays an important role in constructing the coherent excitonic energy transfer. It is also found that the symmetry breaking caused by the dimerization of bacteriochlorophylls and coherence or correlation between two rings will be conducive in enhancing the exciton transfer efficiency.